Investigation on the transient response of a speed-varying rotor with sudden unbalance and its application in the unbalance identification. Issue 4 (December 2020) - Xia, Yebao; Ren, Xingmin; Qin, Weiyang; Yang, Yongfeng; Lu, Kuan; Fu, Chao
It is well known that the sudden unbalance is harmful for rotor systems, since it is in huge amount and has a strong impact. Thus, it is difficult to identify the unbalance from the sudden unbalance response of rotor and very few studies have been done on this topic. This paper focuses on the transient response characteristics of the speed-varying rotor when the sudden unbalance occurs, and the inherent correlation between the unbalance and the transient characteristic quantity. First, different time-dependent functions modelling the loading process of sudden unbalance are derived and compared with the experiment results of the test rotor. The selection principles of function type and duration value are presented. Analyses of transient response characteristics are conducted over the run-up process of the rotor with different parameters of sudden unbalance. Variations of transient response characteristics are summarized into three forms. The varying laws and interrelations of characteristic quantities, and the corresponding parameter region of sudden unbalance are illustrated for each form. Based on the transient analysis results, the momentary positions and angular variations of the rotor disc at some key time instants are illustrated via introducing the key-phase signal. A novel transient-vibration-based method for unbalance identification is proposed. Only a single run-up measurement is required. Numerical experiments verify the effectiveness of the method. In summary, the proposed method can provide a new way for the unbalance identification using the transient response.